Assessment of immunization status among under five children in rural Mangaluru: a cross sectional study - Manglik, Chandana Gopal; N., Shrivathsa Dala (International Journal Of Community Medicine And Public Health, 2019)
Background: Immunization is the process whereby a person is made immune resistant to an infectious disease, typically by the administration of vaccine. If exposure to a disease occurs in a community there is a little to no risk of an epidemic if people have been immunized. This study was to assess the immunization status among children up to 5 years in rural Mangaluru. Methods: A community based cross sectional study was conducted among children of 0-5 years of age group (n=93) in rural Mangaluru using convenient sampling technique. After obtaining oral consent from parents, immunization status of children was assessed using validated questionnaire and details of child found to be partially immunized or not at all, reasons for not giving the vaccine were also collected. Results: 52.7% of the study population was partially immunized and 46.2% were fully immunized; only 83.9% possessed an immunization card. Majority of them have not taken measles/MR (55.9%) and also IPV 1 (46.2%) and Vitamin A2 (61.3%) because of unaware need for further immunization (58%). Conclusions: According to the survey, conducted in rural fields, we found that half of the population was partially immunized. Reasons being lack of awareness, negligence of parents, unaware of 2nd and 3rd dose of vaccines.